2019
DOI: 10.1155/2019/7825804
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Serum Albumin Is Associated with Renal Prognosis in Patients with Diabetic Nephropathy

Abstract: Objective. Although hypoalbuminemia is frequently found in most patients with diabetic nephropathy (DN), its relationship to the severity and progression of DN remains largely unknown. Our aim was to investigate the association between the serum albumin levels and clinicopathological features and renal outcomes in patients with type 2 diabetes mellitus (T2DM) and biopsy-proven DN. Materials and Methods. A total of 188 patients with T2DM and biopsy-proven DN followed up for at least one year were enrolled. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
40
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 41 publications
9
40
0
2
Order By: Relevance
“…Normally, an assault to the body of diabetic patients causes a reduction in the concentrations of total protein and albumin alongside increase in total bilirubin concentration. [62] The results of this study agreed with the works of Iwasaki et al, [63] Gonz alez-Pacheco et al, [64] Zhang et al [65] and Zhu et al [66] The high concentration of bilirubin in diabetic group of experimental rats as found in our study shows that a damage to the liver leads to the release of bilirubin into the bloodstream causing the levels to increase with reduction in the level of albumin and total protein. The impact of K. africana will be to normalize the levels of these biochemical biomarkers.…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 92%
“…Normally, an assault to the body of diabetic patients causes a reduction in the concentrations of total protein and albumin alongside increase in total bilirubin concentration. [62] The results of this study agreed with the works of Iwasaki et al, [63] Gonz alez-Pacheco et al, [64] Zhang et al [65] and Zhu et al [66] The high concentration of bilirubin in diabetic group of experimental rats as found in our study shows that a damage to the liver leads to the release of bilirubin into the bloodstream causing the levels to increase with reduction in the level of albumin and total protein. The impact of K. africana will be to normalize the levels of these biochemical biomarkers.…”
Section: Discussion and Conclusion Discussionsupporting
confidence: 92%
“…As expected, and found in many studies, serum albumin concentrations were inversely associated with decline in eGFR and high risk of adverse renal outcomes [34][35][36][37]. Similarly, the inverse relationship between haemoglobin and decline in eGFR and poor renal outcomes is expected.…”
Section: Discussionsupporting
confidence: 75%
“…Studies have shown that younger age [17], dyslipidaemia [18], lower albumin [19], lower Hb [20] and proteinuria [21] are associated with CKD progression and all these factors were predictive of patients having rapid linear progression in our analysis. The observation of younger patients at more at risk of progression may be due to the underlying age differences in CKD aetiology [22].…”
Section: Discussionmentioning
confidence: 56%